Deleting Titin’s C-Terminal PEVK Exons Increases Passive Stiffness, Alters Splicing, and Induces Cross-Sectional and Longitudinal Hypertrophy in Skeletal Muscle - van der Pijl, Robbert J.; Hudson, Brian; Granzier-Nakajima, Tomotaroh; Li, Frank; Knottnerus, Anne M.; Smith, John; Chung, Charles S.; Gotthardt, Michael; Granzier, Henk L.; Ottenheijm, Coen A. C. (Frontiers in Physiology, 2020)
The Proline, Glutamate, Valine and Lysine-rich (PEVK) region of titin constitutes an entropic spring that provides passive tension to striated muscle. To study the functional and structural repercussions of a small reduction in the size of the PEVK region, we investigated skeletal muscles of a mouse with the constitutively expressed C-terminal PEVK exons 219-¬¬225 deleted, the TtnΔ219¬¬225 model (MGI: Ttntm2.1Mgot). Based on this deletion, passive tension in skeletal muscle was predicted to be increased by 17% (sarcomere length 3.0 µm). In contrast, measured passive tension (sarcomere length 3.0 µm) in both soleus and EDL muscles was increased 53 ± 11% and 62 ± 4%, respectively. This unexpected increase was due to changes in titin, not to alterations in the extracellular matrix, and is likely caused by co-¬¬expression of two titin isoforms in TtnΔ219-225 muscles: a larger isoform that represents the TtnΔ219-225 N2A titin and a smaller isoform, referred to as N2A2. N2A2 represents a splicing adaption with reduced expression of spring element exons, as determined by titin exon microarray analysis. Maximal tetanic tension was increased in TtnΔ219¬¬225 soleus muscle (WT 240 ± 9; TtnΔ219¬¬225 276 ± 17 mN/mm2), but was reduced in EDL muscle (WT 315 ± 9; TtnΔ219-225 280 ± 14 mN/mm2). The changes in active tension coincided with a switch towards slow fiber types and, unexpectedly, faster kinetics of tension generation and relaxation. Functional overload (FO; ablation) and hindlimb ¬¬suspension (HS; unloading) experiments were also conducted. TtnΔ219¬¬225 mice showed increases in both longitudinal hypertrophy (increased number of sarcomeres in series) and cross-¬sectional hypertrophy (increased number of sarcomeres in parallel) in response to FO and attenuated cross-sectional atrophy in response to HS. In summary, slow-¬ and fast-twitch muscles in a mouse model devoid of titin’s PEVK exons 219-¬¬225 have high passive tension, due in part to alterations elsewhere in splicing of titin’s spring region, increased kinetics of tension generation and relaxation, and altered trophic responses to both functional overload and unloading. This implicates titin’s C-¬-terminal PEVK region in regulating passive and active muscle mechanics and muscle plasticity.